Asuhan Keperawatan pada Keluarga yang Mengalami Perubahan Nutrisi Kurang Dari Kebutuhan Tubuh dengan Diabetes Melitus Di Puskesmas Pinang Ranti, Jakarta - Artikan Zebua; Herlina Herlina (STIKes Persada Husada Indonesia, 2022)
Diabetes mellitus is a chronic disease that occurs when the pancreas can not produce insulin that has been in the production. Health development as one of the national development efforts aimed at the creation of awareness, willingness and ability to live healthy every inhabitant so as to have optimal health degree. One way to achieve this is to provide nursing care to family and community individuals. Based on the visit of patients who come to Pinang Ranti Health Center in 2017 that is in January-December 2017, diabetes mellitus 937 inhabitants. The objective of the study was to obtain a description of nursing care in families who experienced less nutritional change than the body needs with diabetes mellitus. The design of this research is qualitative descriptive with case study approach with intervention. Data collection includes interview, observation, physical examination, documentation study and literature study. The result of nursing care got priority diagnosis that is less nutrition change from body requirement with diabetes mellitus at family of Tn. D and Ny. D. the action plan undertaken consists of TUK I-V, the family appears to be cooperative. Conclusions in families 1 and 2 alike found a diagnosis of nutritional changes less than body requirements associated with family inability to care for family members with diabetes mellitus and in the assessment of the authors found no obstacles because the family is very cooperative. Suggestions for family Tn. D and family Ny. D are expected to routinely bring family members to regularly check the health of the health center or other health services, and continue to perform nursing actions that have been agreed.